POST SOVIET COUNTRIES’ FOREIGN TRADE ANALYSIS: GRAVITY METHOD - N. Chernov (Вестник университета)
In the article the foreign trade analysis of post soviet countries such as Kazakhstan and Ukraine based on gravity model is presented. The results of calculations of designed model, evaluations of impact of various factors on foreign trade flows of studied countries and evaluations of cooperation with various integration blocks are given. Changes of factor’s impact and interactions with integration associations in dynamics and without main export products with low degree of processing are considered. Conclusions of studied countries’ foreign trade features are formulated.